Pengaruh Literasi Keuangan Ibu Rumah Tangga Terhadap Perilaku Pengelolaan Keuangan Keluarga Dimoderatori Tingkat Pendidikan dan Pekerjaan - Putri Aifa Nur Amida; Leny Noviani; Dini Octoria (Jurnal Pendidikan Ekonomi (JUPE), 2022)
This study aims to determine the effect of housewives' financial literacy on the behavior of family financial management by moderating the level of education and work in Mojo District, Kediri Regency. Determination of the research method is descriptive quantitative with research subjects housewives in Mojo District, Kediri Regency totaling 384 respondents. The sampling technique is non-probability sampling using convenience sampling technique by distributing questionnaires or questionnaires. The data analysis technique used in this research is Moderated Regression Analysis (MRA). The results obtained indicate that: (1) the financial literacy of housewives has a significant effect on the behavior of family financial management in Mojo District, Kediri Regency. (2) the financial literacy of housewives with a moderate level of education has a significant effect on the behavior of family financial management in Mojo District, Kediri Regency. (3) the financial literacy of housewives with a work moderator has no significant effect on the behavior of family financial management in Mojo District, Kediri Regency.